Childhood cancer incidence patterns by race, sex and age for 2000–2006: A report from the South African National Cancer Registry. Issue 11 (21st November 2014) - Erdmann, Friederike; Kielkowski, Danuta; Schonfeld, Sara J.; Kellett, Patricia; Stanulla, Martin; Dickens, Caroline; Kaatsch, Peter; Singh, Elvira; Schüz, Joachim
<x xml:space="preserve">Abstract</x> Higher childhood cancer incidence rates are generally reported for high income countries although high quality information on descriptive patterns of childhood cancer incidence for low or middle income countries is limited, particularly in Sub‐Saharan Africa. There is a need to quantify global differences by cancer types, and to investigate whether they reflect true incidence differences or can be attributed to under‐diagnosis or under‐reporting. For the first time, we describe childhood cancer data reported to the pathology report‐based National Cancer Registry of South Africa in 2000–2006 and compare our results to incidence data from Germany, a high income country. The overall age‐standardized incidence rate (ASR) for South Africa in 2000–2006 was 45.7 per million children. We observed substantial differences by cancer types within South Africa by racial group; ASRs tended to be 3–4‐fold higher in South African Whites compared to Blacks. ASRs among both Black and White South Africans were generally lower than those from Germany with the greatest differences observed between the Black population in South Africa and Germany, although there was marked variation between cancer types. Age‐specific rates were particularly low comparing South African Whites and Blacks with German infants. Overall, patterns across South African population groups and in comparison to Germans were similar for boys and girls. Genetic and environmental reasons may probably explain rather a small proportion of the observed differences. More research is needed to understand the extent to which under‐ascertainment and under‐diagnosis of childhood cancers drives differences in observed rates.